Existence Theorem for the Prices Fixed Point Problem of the Overlapping Generations Model, Via Metric Spaces Endowed with a Graph (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The aim of this paper is to study the existence of the solution for the overlapping generations model, using fixed point theorems in metric spaces endowed with a graph. The overlapping generations model has been introduced and developed by Maurice Allais (1947), Paul Samuelson (1958), Peter Diamond (1965) and so on. The present paper treats the case presented by Edmond (2008) in (Edmond, 2008) for a continuous time. The theorem of existence of the solution for the prices fixed point problem derived from the overlapping generations model gives an approximation of the solution via the graph theory. The tools employed in this study are based on applications of the Jachymski fixed point theorem on metric spaces endowed with a graph (Jachymski, 2008).